Heme Dependent Catalase Conditionally Contributes to Oxygen Tolerance of Tetragenococcus halophilus Strains Isolated from Soy Sauce Moromi - Jialian Li; Bo Wang; Jian Chen; Guocheng Du; Fang Fang (Applied Sciences, 2022)
Tetragenococcus halophilus strains are the halophilic lactic acid bacteria (LAB) that are present in microbial communities during soy sauce or other hyperosmotic foods’ fermentation. This species contributes to the formation of volatiles in fermented foods but may experience harsh conditions such as oxidative stress and osmotic stress during fermentation. The characterization of the oxygen tolerance of T. halophilus and elaboration of its antioxidant mechanism are important for the selection of suitable LAB for food fermentation. In this work, the growth of T. halophilus strains isolated from soy sauce moromi under both aerobic and anaerobic conditions was compared, and the function of their antioxidant enzymes was investigated. These strains showed differences in oxidation resistance, and they all produce antioxidant enzymes including superoxide dismutase, peroxidase and glutathione reductase. Interestingly, genes encoding catalase (CAT) are present in the genome of T. halophilus strains, though some of them are pseudogenes. Catalase produced by T. halophilus belongs to the heme-dependent CAT, and its activity could only be detected in the presence of heme under aerobic condition. The CAT from T. halophilus conditionally contributes to resistance to hydrogen peroxide and oxidative stress. These results elucidated the possible antioxidant mechanism of T. halophilus and revealed the differences in the oxidative stress tolerance of T. halophilus strains.